KARAKTERISTIK BIOFISIK HABITAT TARSIUS (Tarsius pumilus) DI GUNUNG ROREKATIMBU KAWASAN TAMAN NASIONAL LORE LINDU SULAWESI TENGAH - Sandego, Jemi Yanto; Ningsih, Sri; Ihsan, Moh (Warta Rimba, 2014)
Tarsius (Tarsius pumilus) is the smallest mammals in the world and some of the species are classified to the endemic species of Sulawesi island, Indonesia. Tarsius is a member of tarssidae family. The aims of this study were to determine bio-physics characteristics of tarsius habitats at the mount Rorekatimbu. Research was performed as field research at Mount Rorekatimbu, Lore Lindu National Park, Central Sulawesi. This research was conducted from February through April 2014.Ninet sample plots were made by the size of 20x20 m. Ploting was done by purposive sampling method around tarsius habitats.Hence vegetation date were analysed to determine the density, frequency, dominant, and Importance Value Index.The results showed that the highest importance value index (IVI) at the tree and pole level was Castanopsis acuminatissima (Blume) A.DC with the value 109,88% and 71,74%, respectively. At the sapling level, the highest IVI was achieved by Pinanga cease Blume with the value 80,90%, and at the seedling level, the highest IVI was achieved by Calamus sp with the value 36,77%. Furthermore, the abiotic condition of the habitat including; temperature (14ÂºC-20ÂºC) and relative humidity (64%-83%) and located at 2031mtill 2084 m asl. Key words: Â Habitat, Tarsius pumilus, Endemic, Mount Rorekatimbu, Lore Lindu National Park